rpoN1, but not rpoN2, is required for twitching motility, natural competence, growth on nitrate, and virulence of Ralstonia solanacearum - Ray, Suvendra K.; Kumar, Rahul; Peeters, Nemo; Boucher, Christian; Genin, Stephane (Frontiers in Microbiology, 2015)
The plant pathogen Ralstonia solanacearum has two genes encoding for the sigma factor 54: rpoN1, located in the chromosome and rpoN2, located in a distinct ‘megaplasmid’ replicon. In this study, individual mutants as well as a double mutant of rpoN were created in R. solanacearum strain GMI1000 in order to determine the extent of functional overlap between these two genes. By virulence assay we observed that rpoN1 is required for virulence whereas rpoN2 is not. In addition rpoN1 controls other important functions such twitching motility, natural transformation and growth on nitrate, unlike rpoN2. The rpoN1 and rpoN2 genes have different expression pattern, the expression of rpoN1 being constitutive whereas rpoN2 expression is induced in minimal medium and in the presence of plant cells. Moreover, the expression of rpoN2 is dependent upon rpoN1. Our work therefore reveals that the two rpoN genes are not functionally redundant in R.solanacearum. A list of potential sigma 54 targets was identified in the R. solanacearum genome and suggests that multiple traits are under the control of these regulators. Based on these findings, we provide a model describing the functional connection between RpoN1and the PehR pathogenicity regulator and their dual role in the control of several R. solanacearum virulence determinants.